2021
DOI: 10.1186/s12891-021-04049-3
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcome after posterior stabilization of unstable Midthoracic spine fractures in the elderly

Abstract: Background The evidence for the treatment of midthoracic fractures in elderly patients is weak. The aim of this study was to evaluate midterm results after posterior stabilization of unstable midthoracic fractures in the elderly. Methods Retrospectively, all patients aged ≥65 suffering from an acute unstable midthoracic fracture treated with posterior stabilization were included. Trauma mechanism, ASA score, concomitant injuries, ODI score and radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous studies have reported on the advantages and nuances of this technique; however, despite some similarities of the surgical approach, these studies focused on degenerative diseases or kyphoplasty rather than instrumentation for unstable fractures, and some of them treated under general anesthesia. 10,27,28 The closest related study is the one written by Chopko; in his study, he conducted percutaneous decompression, vertebral fixation, and fusion in 13 patients having spondylopathy and lower back pain under sedation in a neuroangiography room. All the patients presented a very high risk for general anesthesia as determined by related comorbidities and patient age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported on the advantages and nuances of this technique; however, despite some similarities of the surgical approach, these studies focused on degenerative diseases or kyphoplasty rather than instrumentation for unstable fractures, and some of them treated under general anesthesia. 10,27,28 The closest related study is the one written by Chopko; in his study, he conducted percutaneous decompression, vertebral fixation, and fusion in 13 patients having spondylopathy and lower back pain under sedation in a neuroangiography room. All the patients presented a very high risk for general anesthesia as determined by related comorbidities and patient age.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Other studies disagree with this, and reports of improved clinical and radiologic outcomes after surgery also exist. 9,10 In cases in which an unstable fracture is present, the current literature is inconclusive regarding treatment of elderly patients because of the high risk that this population represents. For instance, Mao et al described an increased risk for medical complications in patients older than 80 years who underwent surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, an additional CT was carried out in patients with signs of vertebral fractures after low and moderate energy trauma, which was done in 4% of the patients. The trauma mechanism was analyzed and divided into low energy trauma, moderate energy trauma, and high energy trauma in accordance to Spiegl et al [9]. Additionally, fractures that could not be remembered were defined as insufficiency fractures.…”
Section: Methodsmentioning
confidence: 99%
“…Relevant kyphotic malalignment leads to an increase rate of subsequent vertebral body fractures due to increased biomechanical stress first of all at the adjacent vertebral bodies and secondly in the midthoracic spine [8]. However, studies have shown unexpected high rates of subsequent vertebral body fractures after posterior stabilization despite low to moderate loss of reduction [6,9]. Additionally, subsequent vertebral fractures were associated with worse clinical outcome after operative stabilization [6].…”
Section: Introductionmentioning
confidence: 99%